2005
DOI: 10.1182/blood-2004-12-4935
|View full text |Cite
|
Sign up to set email alerts
|

A functional analysis of the putative polymorphisms A91V and N252S and 22 missense perforin mutations associated with familial hemophagocytic lymphohistiocytosis

Abstract: Up to 60% of cases of the autosomal recessive immunodeficiency hemophagocytic lymphohistiocytosis (HLH) are associated with mutations in the perforin (PRF1) gene. In this study, we expressed wild-type and mutated perforin in rat basophil leukemia cells to study the effect on lytic function of the substitutions A91V and N252S (commonly considered to be neutral polymorphisms) and 22 perforin missense substitutions first identified in HLH patients. Surprisingly, we found that A91V perforin was expressed at reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 28 publications
6
116
4
Order By: Relevance
“…Studies based on analysis of cytotoxic lymphocytes from A91V carriers or rat basophil leukemia cells transfected with variants of the perforin cDNA have shown that A91V decreases perforin function by altering its conformation, decreasing its cleavage to the active form and increasing its degradation. 16,17 Risma et al 18 classified A91V as a class 1 missense mutation with limited functional impact that allows partial maturation of the protein. Voskoboinik et al 19 have recently used a complementation assay with perforin-knockout primary CTL to show that A91V reduces both the steady-state level of perforin expression in effector cells ('presynaptic' dysfunction) and its intrinsic lytic capacity on target cells, and also displays some dominant-negative effect on the wild-type protein ('postsynaptic' dysfunction).…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on analysis of cytotoxic lymphocytes from A91V carriers or rat basophil leukemia cells transfected with variants of the perforin cDNA have shown that A91V decreases perforin function by altering its conformation, decreasing its cleavage to the active form and increasing its degradation. 16,17 Risma et al 18 classified A91V as a class 1 missense mutation with limited functional impact that allows partial maturation of the protein. Voskoboinik et al 19 have recently used a complementation assay with perforin-knockout primary CTL to show that A91V reduces both the steady-state level of perforin expression in effector cells ('presynaptic' dysfunction) and its intrinsic lytic capacity on target cells, and also displays some dominant-negative effect on the wild-type protein ('postsynaptic' dysfunction).…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44] However, several studies have reported functional consequences of this variant including decreased PRF1 expression, reduced lytic activity, and impaired NK cell-mediated cytotoxicity. [45][46][47][48] Additionally, functional prediction models including Polyphen-2 and the sorting intolerant from tolerant (SIFT) algorithm imply that this change is damaging. Primary HLH and secondary HLH have historically been considered separate entities; however, these new genetic insights and the observation that primary HLH is often set off by a trigger suggest that there may be more overlap than previously recognized.…”
Section: 27mentioning
confidence: 99%
“…The A91V mutation affects PRF folding and stability within the effector cell, and as a result greatly reduces its intrinsic cytolytic activity. [79][80][81] However, within the environment of PRF-deficient CTLs, the mutant recovered 30-50% of the wild-type PRF activity. 80 Interestingly, in vitro A91V also displayed a mild dominant-negative effect.…”
Section: A91v Polymorphism Of Perforinmentioning
confidence: 99%